Seroprevalence and risk factors for sheep pox and goat pox among small ruminant herds from Nakapiripirit and Sembabule districts, Uganda - Gerald, Nizeyimana; Chrisostom, Ayebazibwe; Savino, Biryomumaisho; Franklin, Mayanja; Dennis, Muhanguzi; Patrick, Vudriko; Robert, Tweyongyere; Joseph, Erume (Frontiers in Veterinary Science, 2025)
BackgroundSheep pox and goat pox diseases[SP&GP] caused by sheep poxvirus and goat poxvirus, respectively are transboundary, World Organization for Animal Health class A-notifiable viral diseases. In Uganda, despite the inevitable national underreporting, suspected sheep pox and goat pox outbreaks have been reported from passive surveillance. There are limited sheep pox and goat pox serological data in small ruminants in Uganda.Materials and methodsA cross-sectional study was conducted in Sembabule and Nakapiripirit Districts, largely representing semi-intensive and communal/pastoral small ruminant production systems, respectively, between May and September 2023 to (i) determine the seroprevalence of sheep pox and goat pox virus antibodies in goats and sheep and (ii) identify the risk factors for the spread and transmission of SP&GP in small ruminant herds. A total of 1,515 serum samples were collected from 63 farms/clusters in Sembabule [N = 703] and Nakapiripirit [N = 812] districts and analyzed using Double Capripox multispecies antigen ELISA test to detect SP&GPV antibodies. Univariate and bivariate statistical analyses for animal and farm/cluster level factors were performed for significance using chi square and Fisher’s exact tests, respectively.ResultsOf the total samples tested, [n = 137, 10%; CI, 8.5–13.1%] were positive for S&GP antibodies. Seropositivity was greater in Nakapiripirit [n = 93, 12%] than in Sembabule districts [n = 44, 6%]. Although low in proportion, overall, from both districts, seropositivity among sheep [N = 296, n = 32,12%] was higher than goats [N = 1,219, n = 105,10%]. Age, sex, type of epidemiologic unit, gifting of animals and species (p < 0.05) were associated with S&GP seropositivity. However, at multivariable level, only age [OR (95% CI), p-value: 0.43 (0.21–0.87), 0.019], and sex [OR (95% CI), p-value, 2.14 (1.31–3.5), 0.003] were independently associated with S&GP seropositivity.ConclusionThis study confirmed exposure to SP&GPV in goats and sheep to varying degrees in the districts studied. We recommend, based on evidence, an extended nationwide evaluation of antibody seroprevalence in goats and sheep to inform national-level SP&GP control efforts. To the best of our knowledge, this is the first documented systematic study to evaluate the seroprevalence of S&GPV antibodies in sheep and goats in the two districts.